Program Program Layanan Bimbingan dan Konseling sebagai Pencegahan Bullying di Sekolah - Nailul Fauziyah (Syifaul Qulub: Jurnal Bimbingan dan Konseling Islam, 2022)
This article provides a theoretical conceptualization of guidance and counseling service programs as bullying prevention in schools. Bullying is a form of violence perpetrated by the strong against the weak. The phenomenon of bullying is not a new phenomenon we have seen. However, in the current disruptive era, bullying behavior is increasingly prevalent and is a phenomenon that deserves serious attention from various parties. Bullying behavior causes various psychological and physical impacts as well as impacts on the peace of life of victims of bullying. The impact can be short term or long term. Some forms of bullying behavior are physical bullying, verbal bullying, relational bullying and cyber bullying. Bullying behavior can be found in various places, including at school. Schools that are supposed to be places to optimize the development of students' self-potential have turned into places that are torturous and scary for those who are victims and witnesses of bullying. Seeing the phenomenon of bullying that is increasingly happening in schools, it is considered necessary to prevent bullying in the school environment. One of them is through the guidance and counseling service program in schools. Guidance and counseling services which are an integral part of the entire educational process in schools that assist students in achieving optimal self-development and assist students in dealing with difficulties and challenges at school. Bullying can be prevented by several integrated services contained in the guidance and counseling which consist of basic guidance services, responsive services, individual planning services and system support. Keyword : Guidance and Counseling,Bullying.